Peach (Prunus Persica) Fruit Response to Anoxia: Reversible Ripening Delay and Biochemical Changes - Lara, María Valeria (2011)
The use of modified atmospheres has been successfully applied in different fruits to delay the ripening process and to prevent physiological disorders. In addition, during normal ripening, hypoxic areas are generated inside the fruit; moreover, anaerobic conditions may also arise during fruit post-harvest storage and handling. In consequence, the fruit is an interesting model to analyze the metabolic modifications due to changes in oxygen levels. In this work, a 72 h anoxic treatment by using an N2 storage atmosphere was applied to peaches (Prunus persica L. Batsch) after harvest. Ripening was effectively delayed in treated fruits, preventing fruit softening, color changes and ethylene production. Metabolic changes induced by anoxia included induction of fermentative pathways, glycolysis and enzymes involved in both sucrose synthesis and degradation. Sucrose, fructose and glucose contents remained unchanged in treated fruit, probably due to sucrose cycling. Sorbitol was not consumed and citrate was increased, correlating with citric acid cycle impairment due to O2 deprivation. Malate content was not affected, indicating compensation in the reactions producing and consuming malate. Changes in malic enzymes and pyruvate orthophosphate dikinase may provide pyruvate for fermentation or even act to regenerate NADP. After fruit transfer to aerobic conditions, no signs of post-anoxia injury were observed and metabolic changes were reversed, with the exception of acetaldehyde levels. The results obtained indicate that peach fruit is an organ with a high capacity for anoxic tolerance, which is in accord with the presence of hypoxic areas inside fruits and the fact that hypoxic pre-treatment improves tolerance to subsequent anoxia.